Utilizing community resources of Palawan in the preparation of social studies instructional materials - Bautista, Emma Abiog 1946- (1979)
This study aimed to show how community resources of Palawan can be utilized in the preparation of Social Studies instructional materials. Instructional materials showing how the community resources can be brought to school through the reading materials, illustrations, and suggested additional learning activities as well as how the class can reach the community were made. The conclusion pointed out the importance of community resources to the formation of social studies concepts through the use of instructional materials locally prepared by the researcher.